Can access regulation promote broadband investment and consumer welfare?. (2015) - Avenali, Alessandro; Matteucci, Giorgio; Reverberi, Pierfrancesco
A facility-based firm invests in network quality and sells wholesale local access to two competing downstream firms, which offer vertically differentiated value-added services. We show that, contrary to common wisdom, access price regulation may simultaneously improve consumer welfare and foster investment incentives compared with regulatory forbearance. This result is robust to a number of different model specifications: (i) the bottleneck owner is vertically integrated, and: (a) the regulator can commit before the investment stage, or: (b) there are first-mover advantages, such as consumer switching costs; (ii) the bottleneck owner is vertically separated. We also show that, under access price regulation, consumer welfare and network quality may be higher under vertical separation than under vertical integration.